Updated Views on Neutrophil Responses in Ischemia–Reperfusion Injury. Issue 12 (24th June 2022) - Shepherd, Hailey M.; Gauthier, Jason M.; Terada, Yuriko; Li, Wenjun; Krupnick, Alexander S.; Gelman, Andrew E.; Kreisel, Daniel
Abstract : Ischemia–reperfusion injury is an inevitable event during organ transplantation and represents a primary risk factor for the development of early graft dysfunction in lung, heart, liver, and kidney transplant recipients. Recent studies have implicated recipient neutrophils as key mediators of this process and also have found that early innate immune responses after transplantation can ultimately augment adaptive alloimmunity and affect late graft outcomes. Here, we discuss signaling pathways involved in neutrophil recruitment and activation after ischemia-mediated graft injury in solid organ transplantation with an emphasis on lung allografts, which have been the focus of recent studies. These findings suggest novel therapeutic interventions that target ischemia–reperfusion injury-mediated graft dysfunction in transplant recipients.